Philip Roth, "American pastoral" - Löffler, Philipp (Handbook of the American Novel of the Twentieth and Twenty-First Centuries, 2017)
The essay discusses Philip Roth’s American Pastoral in the context of his ‘American Trilogy’ (also including I Married a Communist [1998] and The Human Stain [2000]). The focus of the essay is on how Roth’s novel imagines the history of the fictional Levov family in pursuit of a broader panorama of the postwar American (upper) middle class. American Pastoral uses the story of Jewish American Seymour “Swede” Levov and his desire to lead an exemplary, self-made American life to explore the limits and possibilities of historical storytelling. The essay examines the novel’s historiographical ambition with a particular emphasis on the modes of storytelling used by the narrator, Nathan Zuckerman, suggesting that American Pastoral appropriates both experimental forms of narration typically associated with high postmodernist fiction and realist forms of narration in the tradition of the nineteenth-century historical novel. The essay concludes by proposing that the novel is best understood in conjunction with the ethical turn in literature that some critics have interpreted as a response to the reduced relevance of postmodernist paradigms of writing.